Contribution to the knowledge of the mayfly genus Teloganella Ulmer, 1939 (Ephemeroptera: Ephemerelloidea) - Kluge, Nikita J.; Selvakumar, C.; Sivaramakrishnan, K. G.; Jacobus, Luke M. (Zootaxa, 2015)
We consider the genus Janohyphella Selvakumar, Sivaramakrishnan & Jacobus, 2014 (Ephemeroptera:Teloganodidae) to be a new junior synonym of Teloganella Ulmer, 1939 [=Janohyphella, syn. n.] based on comparative examination of new and previously studied materials from Malaysia and India. Thus, we propose the following new combination, Teloganella indica, comb. n., and provide new or modified diagnoses for this species, T. umbrata Ulmer, 1939 and the genus Teloganella Ulmer, 1939.